Kesiapsiagaan Generasi Z sebagai Digital Native dalam Arus Informasi Kebencanaan - Feri Ferdinan Alamsyah; Rina Muthia Harahap; Valianty Sariswara; Enjang Pera Irawan; Viena Rizka Aryanto (Jurnal Penelitian Sosial Ilmu Komunikasi, 2026)
Indonesia, as a disaster-prone country, requires effective disaster communication strategies, particularly for Generation Z as digital natives who heavily rely on digital media to access information. This study aims to analyze the use of disaster-related information from media and its implications for information literacy and disaster preparedness among Generation Z. This research employs a quantitative approach using a survey method through an online questionnaire distributed to respondents aged 19–24 years. The sampling technique used is purposive sampling, focusing on individuals who actively use digital media. The collected data were analyzed using descriptive statistics to identify patterns of media usage, levels of trust in information, and the preparedness of respondents in facing disasters. The results indicate that approximately 76% of respondents access disaster information primarily through social media, followed by mass media and official government sources. The level of trust in information is relatively high, 74% of respondents trusting information from credible sources. In addition, 70 percent of respondents perceive spatial-based information, such as risk maps and real-time notifications, as easier to understand compared to textual information. However, practical preparedness remains relatively low, with few respondents having evacuation plans and limited participation in disaster simulation exercises. These findings reveal a gap between access to information and actual preparedness. This study highlights that the effectiveness of disaster communication depends not only on media platforms but also on message delivery strategies that are educational, practical, and action-oriented.